PERSEPSI MAHASISWA FAKULTAS EKONOMI MENGENAI PENGGELAPAN PAJAK (STUDI PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS WIJAYA KUSUMA SURABAYA) - James Tumewu; Wiwin Wahyuni (Universitas Pakuan, 2018)
Tax evasion is a tax deductible scheme that is owed by violating the provisions of taxation (illegal). Tax evasion is usually done by the company by making false invoices, not recording some sales, or preparing fake financial statements, but the practice of tax evasion like this is often caught, thus the mode of tax evasion is now changing. Perception is the response of something or is the process of knowing some things through the senses. This research is interested to prove the perception of the students of economics faculty regarding the tax evasion, where these students have received taxation class and practice. This study uses questionnaires to obtain students perception data, and use purposive sampling in obtaining sample research. Data analysis technique used is multiple-linear regression. The result of research shows that only discrimination variables affect the tax evasion based on the perception of the students of economics faculty, while the variables of justice, taxation system and understanding of taxation do not affect tax evasion based on the perception of the students of Economics Faculty, Wijaya Kusuma Surabaya University.